An in vitro study on the bleaching capacity of the fresh extract of Citrus Microcarpa, Bunge (Calamansi) on blood-stained endodontically treated maxillary incisors - Almazan, Irene P.
This in vitro study aims to find out the bleaching capacity of the fresh extract of Citrus Micro carpa Bunge (Calamansi) on 21 blood stained endodontically treated maxillary incisors. The original shades were photographed, after which a centrifuge machine was utilized for staining the teeth and the resultant stained teeth were photographed. 3 bleaching methods namely: Thermocatalytic, Walking Bleach and Combination of both methods were used in bleaching these stained teeth. Based on the results, as seen through the 3 photographs taken for each tooth (original, stained and bleached); 5 teeth were bleached or 24% of the total; 14 teeth were partly bleached or 66% and 2 teeth were unbleached or 10%. It can therefore be concluded that the fresh extract of calamansi is an effective bleaching agent on blood stained endodontically treated maxillary incisors.